Crafting Purity in Assyro-Babylonian Procedures: Time, Space, and the Material World - Borrelli, Noemi; Escobar, Eduardo A. (ARYS. Antigüedad: Religiones y Sociedades, 2022)
Assyro-Babylonian procedural texts for making cult objects dated to the 1st millennium BCE provide an untapped resource for examining scribal conceptions of craft and purity in the ancient world. Ritual procedures for “opening of the mouth” of a cult statue (mīs pî), and for manufacturing a ritual drum called the lilissu, constitute the principal focus of this two-part study. This work uses three themata – time, space, and the material world – to provide the scaffolding for a comparative analysis that spans various centuries and localities, highlighting the ways in which “purity” was crafted in cuneiform scholarly cultures.
Keywords: Assyriology; craft production; cult objects; cuneiform studies; history of knowledge; history of science; history of technology; history of the ancient Near East; procedures; purity; recipes; religion